Management of pyloric stenosis in children - S. Shehab Aljomaily, Fawzi (Tikrit Journal of Pharmaceutical Sciences, 2023)
A prospective study of 24 cases of infantile hypertrophic pyloric stenosis in Salahaldeen government from February 2008-february 2011. All patients evaluated according to family history, sex, age, age at starting of vomiting and hydration state. Examination done for any palpable mass and sign of dehydration, and muscle wasting ,feeding test done for all patients. Patients admitted to hospital and investigations done which includes complete blood picture, blood urea, serum electrolyte. All patients send for ultrasound study of the pyloric canal to evaluate the length and thickening of the pyloric canal and consider as appositive study if the length more than 14mm and thickening more than 4mm pyloromyotomy done for all case with very good result and most of patient discharge after 24h of surgery.